Defending rights in contemporary China - Benney, Jonathan (London ; New York : Routledge, 2013)
"Citizen rights defence campaigns reflect the changing lives and priorities of Chinese citizens, both urban and rural. The term weiquan, or rights defence, was first coined by the Chinese party-state as part of a process of promotion of various laws, and was thus used by government-affiliated organisations to promote the rights of women, children, and consumers, and to develop citizens' legal awareness. Subsequently, first private citizens, then groups of citizens, then lawyers, appropriated the term as a means of dispute resolution in areas such as private property rights, rights for the handicapped, corruption claims and grievances with officials. Rights defence is important not just because of the political ramifications of its campaigns, but also because of the strategies its activists have used. Rights defence campaigns have taken novel forms unprecedented in China, including the use of the Internet by rights campaigners, the development of rights entrepreneur (or people who have set up businesses linked to rights defence), and the selection of representatives and leaders in rights defence campaigns. In recent years, the idea of rights defence has become used as a tool to attack the party-state, specifically by lawyers and legal campaigners. The growth of rights defence movements reflects the increasing capacity of Chinese citizens to shape their own civic discourse to achieve diverse goals. While rights defence may not pose an immediate threat to the authority of the party-state, it is nonetheless an important symbol of a developing social pluralism in China. This book offers essential insight into the development of rights in contemporary China and will be highly relevant for students, scholars and specialists in legal developments in Asia as well as anyone interested in social movements in China"--
Includes bibliographical references (pages [175]-192) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Civil rights -- China; Civil rights -- Social aspects -- China; Civil rights -- Political aspects -- China; Electronic books